The Chinese garden - Wang, Joseph C (Images of Asia., 1998)
Whether built for imperial use or for the enjoyment of a private scholar and his family, the garden is a centerpiece of classical Chinese culture. This book draws on a wide range of literary and artistic sources to present the fundamentals of Chinese garden design. Illustrated with photographs showing detailed views of sites in Suzhou and Yangzhou, Shanghai and Beijing, it explains the aesthetic principles and practical concerns of the designer. The "reading" of a Chinese garden that it offers is enriched by a greater understanding of the literary and artistic conventions involved in the gardens construction.